Odyssey of the Mind: Social Networking in Cyberschool - Michael K. Barbour; Cory Plough (International Review of Research in Open and Distributed Learning, 2012)
K-12 online learning and cyber charter schools have grown at a tremendous rate over the past decade. At the same time, these online programs have struggled to provide the social spaces where students can interact that K-12 schools are traditionally able to provide. Social networking presents a unique opportunity to provide these kinds of social interactions in an online environment. In this article, we trace the development and use of social networking at one cyber charter school to extend the space for online instruction and provide opportunities for social interaction that online schools are often unable to provide.